Effect of U-Pace Instruction on Academic Success, Learning, and Perceptions in Younger and Older Undergraduates. Issue 1 (2nd January 2018) - Fleming, Raymond; Barth, Dylan; Weber, Nicole; Pedrick, Laura E.; Kienzler, Sarah E.; Reddy, Diane M.
ABSTRACT: A randomized controlled trial was conducted to determine the efficacy of U-Pace instruction for older undergraduates, ages 25 and older, and younger undergraduates, ages 18 to 24. Additionally, change in learner perceptions across the semester, an outcome not reported in the literature on U-Pace instruction, was investigated. In both younger and older undergraduates U-Pace instruction produced greater learning, greater academic success, and sustained or improved students' perceptions of themselves as learners compared with Face-to-Face instruction. The findings provide strong support for the efficacy of U-Pace instruction in younger and older students and highlight a possible mechanism underlying U-Pace instruction's effects on learning and academic success.